TEKNIK DAN FUNGSI PENERJEMAHAN KATA UMPATAN PADA NOVEL RIḤLAH ILĀ ALLĀH - Baking, Aad Nur Sayyidus Syuhuur; Sajarwa, Sajarwa (Sunan Kalijaga State Islamic University Yogyakarta, 2023)
This study aims to find out the translation techniques of swear words in the novel Riḥlah ilā Allāh by Najib Kaelani and the function of those swear words. The data in this study are in the form of swear words and their translations which are sourced from the novel Riḥlah ilā Allāh and its translation